Research on Web-based Real-time Monitoring System on SVG and Comet - Lijing Zhang; Wei Xiong; Xuehui Xian (Institute of Advanced Engineering and Science, 2012)
For the lack of real-time performance of browser technology in existing Web-based real-time monitoring system, takes use of SVG (Scalable Vector Graphics) and the Comet to design a new Web-based real-time monitoring system. In this system, JSON (JavaScript Object Notation) is the data transmission carrier, Comet is the key technology for system communication and data transmission, and SVG is a chart drawing tool in the browser side. So this system has a good real-time and is rich in the form of show. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1347